A case report of trisomy 16 with mosaicism with intrauterine growth restriction - Saleem, Raisham; Mehboob, Rabia; Aupont, Jean; Ahmed, Mustafa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Trisomy 16 is one the common cause of miscarriages in the 1st and 2nd trimesters. Trisomy 16 mosaicism is rarely detected by amniocentesis in the second trimester. Intrauterine growth restriction (IUGR) is one of the common outcomes of mosaic trisomy 16. Hence, we report a case of trisomy 16 mosaicism diagnosed by the cytogenetic analysis of amniotic fluid cells. The baby had an intrauterine growth restriction and interestingly her karyotype was normal. As trisomy 16 mosaic fetuses does not have a characteristic phenotype, it is recommended to inform the possibility of mosaicisms including this trisomy 16 mosaicism during prenatal genetic diagnosis and genetic counselling for parents.